The Effect Of Service Quality And Customer Satisfaction On Customer Loyalty At Coffee Flamboys Roaster Bandar Lampung - Ardansyah, Ardansyah; Muhammad Ferdiansyah asari (Cita konsultindo, 2025)
This study aims to analyze the effect of service quality and customer satisfaction on customer loyalty at Coffee Flamboys Roaster, Bandar Lampung. Using quantitative methods and multiple regression analysis, this study involved 83 respondents selected through purposive sampling technique. The analysis results show that service quality has a positive and significant effect on customer loyalty, with a regression coefficient of 0.471. In addition, customer satisfaction also contributes positively to customer loyalty with a coefficient of 0.347. Simultaneous analysis shows that these two independent variables together have a significant influence on customer loyalty, with the R² value indicating a substantial contribution to the variation in loyalty. These findings emphasize the importance of improving service quality and customer satisfaction to build sustainable loyalty. Therefore, it is recommended that Coffee Flamboys Roaster improve product and service quality, and provide training to employees to increase empathy in service. This research provides valuable insights for coffee shop managers in an effort to increase customer loyalty in the midst of intense competition.